2013
DOI: 10.1007/s00277-013-1841-y
|View full text |Cite
|
Sign up to set email alerts
|

“Real-world” data on the efficacy and safety of lenalidomide and dexamethasone in patients with relapsed/refractory multiple myeloma who were treated according to the standard clinical practice: a study of the Greek Myeloma Study Group

Abstract: Lenalidomide and dexamethasone (RD) is a standard of care for relapsed/refractory multiple myeloma (RRMM), but there is limited published data on its efficacy and safety in the "real world" (RW), according to the International Society of Pharmacoeconomics and Outcomes Research definition. We studied 212 RRMM patients who received RD in RW. Objective response (≥PR (partial response)) rate was 77.4 % (complete response (CR), 20.2 %). Median time to first and best response was 2 and 5 months, respectively. Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
32
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 26 publications
8
32
3
Order By: Relevance
“…In the Polish group, AEs occurred in 73.2% of patients, and their incidence was comparable to previous reports [10]. The main AE, similarly to reports from the Greek and Spanish groups, was myelosupression, which occurred in 51.6% of patients, including grade 3 and 4 events observed in 16.7% of subjects [6,10].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the Polish group, AEs occurred in 73.2% of patients, and their incidence was comparable to previous reports [10]. The main AE, similarly to reports from the Greek and Spanish groups, was myelosupression, which occurred in 51.6% of patients, including grade 3 and 4 events observed in 16.7% of subjects [6,10].…”
Section: Discussionsupporting
confidence: 88%
“…Our studies demonstrated that LEN is an effective and safe drug in the above mentioned patients. In the entire observation period, the overall response rate (ORR) was 75.5%, and was consistent with findings obtained by Greek and German groups: 73% and 77.4%, respectively [5,10]. It should be noted, however, that in the German group's study LEN + DEX and doxorubicin was used.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations